Ultrasound pupillometry for the detection of a relative afferent pupillary defect (RAPD): Systematic evaluation in patients with optic neuritis and comparison with infrared video pupillometry. - Franziska Siebald; Ulrike Grittner; Carolin Otto; Charlotte Bereuter; Hanna G Zimmermann; Lutz Harms; Jan Klonner; Stephan J Schreiber; Friedemann Paul; Klemens Ruprecht; Felix A Schmidt (PLoS ONE)
Purpose A relative afferent pupillary defect (RAPD) is a characteristic clinical sign of optic neuritis (ON). Here, we systematically evaluated ultrasound pupillometry (UP) for the detection of an RAPD in patients with ON, including a comparison with infrared video pupillometry (IVP), the gold standard for objective pupillometry. Materials and methods We enrolled 40 patients with acute (n = 9) or past (n = 31) ON (ON+), 31 patients with multiple sclerosis (MS) without prior ON, and 50 healthy controls (HC) in a cross-sectional observational study. Examinations comprised the swinging flashlight test, B-mode UP, IVP, autorefraction to assess the best-corrected visual acuity, optical coherence tomography to determine peripapillary retinal nerve fiber layer thickness, and the 51-item National Eye Institute-Visual Function Questionnaire to determine the vision-related quality of life. Results While UP and IVP measurements of pupil diameter (PD) at rest correlated in ON+ eyes (n = 52, r = 0.56, 95% CI: 0.35; 0.72) and in HC eyes (n = 100, r = 0.60, 95% CI: 0.47; 0.72), PD at rest was smaller in UP than in IVP measurements (difference, mean (SD) ON+ eyes: 0.44 (0.87) mm, HC eyes: 0.69 (0.80) mm). RAPD assessment by UP sharply discriminated acute ON eyes (n = 9) and HC eyes (n = 100, AUC = 1, 95%CI: 1; 1). UP detected an RAPD in 5/31 (16%) patients with MS without prior ON who had not exhibited an RAPD during the swinging flashlight test. In ON+ eyes (n = 52), UP showed stronger correlations with visual acuity (r = 0.66, 95% CI: 0.50; 0.78) and vision-related quality of life (r = 0.47, 95% CI: 0.24; 0.66) than IVP (r = 0.52, 95% CI: 0.36; 0.67 and r = 0.27, 95% CI: 0.03; 0.51). Conclusions B-mode UP allows for objective detection and quantification of an RAPD with performance characteristics similar to IVP. RAPD assessment by UP may detect subclinical optic nerve damage in patients with MS. We propose a standardized protocol for RAPD detection by UP that can be used in routine clinical evaluation of patients with ON or other optic neuropathies.